Antecendents Of Hotel Performance With Organizational Ambidexterity As Mediation On Employee of Three Star Hotels In Special Region Of Jakarta - Happy Vanesa, Valentina; Usman, Bahtiar; Oki Berliyanti, Dita (Publisher Cv. Inara, 2024)
The research aims to test and analyze the factors that influence Hotel Employee performance among 3 star hotel employees in Jakarta The unit of analysis is 322 individual employees who work for employees from 10 3-star hotels in Jakarta. Cross-sectional and one-shot data collection was carried out through structured questionnaires distributed via Google Form and also directly. Asymmetric causal research design using quantitative methods. The proposed model includes 123 hypotheses and is tested using Structural Equation Modeling (SEM). The majority of respondents were women aged 20-24 years, with contract employee status, staff positions, working period of less than 5 years with a high school/vocational school/equivalent education level. The results of the test found that Ambidextrous Leadership, Ambidextrous Organizational Culture and Organizational Ambidexterity had a positive influence on Hotel performance while Organizational Ambidexterity had a positive influence from Ambidextrous Leadership and Ambidextrous Organizational Culture The research results can help deepen understanding of the complexity of the relationship between HR Flexibility, ambidextrous, amdixterous leadership and High Performance Work Leadership System on Hotel Employee Performance through organizational Ambidexterity.